2019
DOI: 10.1186/s12978-019-0669-x
|View full text |Cite
|
Sign up to set email alerts
|

Engaging men in an mHealth approach to support postpartum family planning among couples in Kenya: a qualitative study

Abstract: BackgroundInvolving male partners in family planning (FP) education and counseling may improve FP utilization and help meet couples’ reproductive health needs in the postpartum period. We aimed to explore Kenyan men’s and women’s perspectives on an interactive short message service (SMS) approach to support postpartum FP decision-making, and inform intervention content for a randomized controlled trial (RCT).MethodsWe conducted four focus group discussions (FGD) among men (n = 35) and two among pregnant/postpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 48 publications
1
69
0
1
Order By: Relevance
“…However, interview results show that misconceptions and prejudices about the side effects of contraceptive methods are major obstacles that men cite when denying their wives access to FP. In Kenya, Harrington et al 25 identified the side effects and potential harms of contraceptive methods as limiting factors in men's engagement in FP programmes. Previous studies have also shown that husbands' lack of approval and religious beliefs are determining factors for FP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, interview results show that misconceptions and prejudices about the side effects of contraceptive methods are major obstacles that men cite when denying their wives access to FP. In Kenya, Harrington et al 25 identified the side effects and potential harms of contraceptive methods as limiting factors in men's engagement in FP programmes. Previous studies have also shown that husbands' lack of approval and religious beliefs are determining factors for FP.…”
Section: Discussionmentioning
confidence: 99%
“…8 The lack of communication among couples regarding reproductive health and FP issues has long been considered a contributing factor to the unmet need for contraception in SSA. 6,25 Effective FP requires mutual agreement between spouses. This is only possible if both partners understand the concept of FP and the methods available to prevent unintended pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to poor access to affordable interventions and maternal health inequities that are still observed in these countries [11][12][13]. As such, there is a great need to look at varying ways to involve an even wider range of actors in new initiatives, including men's active involvement at different stages of pregnancy to promote positive maternal health outcomes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the study on postpartum women associated with mHealth apps seems insufficient. Postpartum-related mHealth intervention has been investigated and was related to postpartum family planning amongst couples [ 14 , 15 , 16 ] and HIV prevention [ 17 ]. Moreover, globally, one-third of adult women suffer from obesity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%